2017
DOI: 10.1097/md.0000000000006759
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime and recent alcohol use and bone mineral density in adults with HIV infection and substance dependence

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 76 publications
(84 reference statements)
1
14
1
Order By: Relevance
“…The current study results are also are in line with previous studies using the same cohort on the impact of alcohol on bone density which found that alcohol consumption was associated with lower bone density at baseline (Ventura et al, ). However, a change in alcohol consumption was not prospectively associated with change in bone density (Saitz et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study results are also are in line with previous studies using the same cohort on the impact of alcohol on bone density which found that alcohol consumption was associated with lower bone density at baseline (Ventura et al, ). However, a change in alcohol consumption was not prospectively associated with change in bone density (Saitz et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…The metabolic effects of the systemic inflammatory reaction and oxidative stress induced by alcohol are widespread and include muscle wasting and lipoatrophy (Bagby et al, ; Gaddini et al, ; Molina et al, ). Although heavy alcohol consumption is associated with fracture (Kanis et al, ; Zhang et al, ), the effects of alcohol on bone mineral density (Gaddini et al, ) are unclear, particularly in PLWH (Brown et al, ; Saitz et al, ; Sharma et al, ; Ventura et al, ).…”
mentioning
confidence: 99%
“…In the same cohort, Ventura et al. () reported a cross‐sectional, negative association between BMD and recent alcohol consumption, with the strongest association during the postdiagnosis/pre‐ART phase of the HIV care continuum. We did not examine alcohol consumption during different phases (i.e., pre‐HIV, pre‐ART, post‐ART).…”
Section: Discussionmentioning
confidence: 95%
“…Although PEth (which is most effective as a very recent measure of consumption) can help validate these responses, by selecting subjects with high recent drinking levels we may be selecting participants with greater recall bias toward higher AUDIT responses. Subjects were not excluded based on concurrent recreational drug use, which has been considered a confounder in similar analyses (Saitz et al., ; Ventura et al., ). Thus, additional factors related to adverse health effects (with the exception of smoking) have not been fully characterized in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption causes harmful effects on bone density [7] and is related to osteoporosis, due to imbalance in bone repair [8], altering bone microarchitecture, decreasing trabecular and cortical bone thickness, and consequently increasing the risk of fracture [9].…”
Section: Introductionmentioning
confidence: 99%